2017
DOI: 10.1080/14670100.2017.1375238
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pediatric cochlear implant care throughout Europe: Is European pediatric cochlear implant care performed according to guidelines?

Abstract: Regardless of the great heterogeneity in European practice, reasons for latency should be identified on a national level and possibilities to prevent avoidable future implantation delays should be explored to provide national recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
1
7
0
2
Order By: Relevance
“…The present study findings indicated a significant trend towards earlier identification of HL, amplification and initiation of education across the years after implementation of NHSP. This finding was consistent with previous studies (Al-Sayed & Al-Sanosi, 2017;Aras-Öztürk et al, 2018;Bruijnzeel et al, 2017;Wasser, Roth, Herzberg, Lerner-Geva & Rubin, 2019). Comparison of the year periods demonstrated significant decreases in the whole group, GR1 and GR2.…”
Section: Discussionsupporting
confidence: 93%
“…The present study findings indicated a significant trend towards earlier identification of HL, amplification and initiation of education across the years after implementation of NHSP. This finding was consistent with previous studies (Al-Sayed & Al-Sanosi, 2017;Aras-Öztürk et al, 2018;Bruijnzeel et al, 2017;Wasser, Roth, Herzberg, Lerner-Geva & Rubin, 2019). Comparison of the year periods demonstrated significant decreases in the whole group, GR1 and GR2.…”
Section: Discussionsupporting
confidence: 93%
“…As a result of the findings in this line of research, children who are congenitally deaf are receiving implants at an increasingly younger age, with many countries aiming for an implantation within the first 2 years of life ( Bruijnzeel et al 2017 ; Ramsden et al 2012 ).…”
Section: Language Development In Children With Early Cochlear Implantmentioning
confidence: 99%
“…Ustalenie odpowiednich kryteriów kwalifikacyjnych do implantacji ślimakowej jest zawsze przedmiotem niezwykłej troski, szczególnie w odniesieniu do dzieci [25,26]. Nawet nieznaczny ubytek słuchu może być przyczyną opóźnionego rozwoju mowy oraz gorszych osiągnięć szkolnych [27].…”
Section: Wstępunclassified